1988
DOI: 10.1021/bi00417a061
|View full text |Cite
|
Sign up to set email alerts
|

Rotational dynamics of the single tryptophan of porcine pancreatic phospholipase A2, its zymogen, and an enzyme/micelle complex. A steady-state and time-resolved anisotropy study

Abstract: The rotational dynamics of the single tryptophan of porcine pancreatic phospholipase A2 and its zymogen (prophospholipase A2) have been studied by polarized fluorescence using steady-state and time-resolved single-photon counting techniques. The motion of Trp-3 in phospholipase A2 consists of a rapid subnanosecond wobble of the indole ring with an amplitude of about +/- 20 degrees accompanied by slower isotropic rotation of the entire protein. The rotational correlation times for overall particle rotational di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
7
18
0
1
Order By: Relevance
“…We first examined the dansyl fluorescence anisotropy changes to confirm the formation of complex in the low-micromolar range. Fluorescence anisotropy is dependent on the rotational correlation time of fluorophore in the sample, and is often used to reflect the hydrodynamic properties of biomolecules [45]. The increase in anisotropy often arises from slower tumbling of the fluorophore and thus reports the formation of a larger complex.…”
Section: Resultsmentioning
confidence: 99%
“…We first examined the dansyl fluorescence anisotropy changes to confirm the formation of complex in the low-micromolar range. Fluorescence anisotropy is dependent on the rotational correlation time of fluorophore in the sample, and is often used to reflect the hydrodynamic properties of biomolecules [45]. The increase in anisotropy often arises from slower tumbling of the fluorophore and thus reports the formation of a larger complex.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies within the context of interfacial enzyme kinetics and activation have shown such native state heterogeneity for ppPLA 2 and the prominent role of its N-terminus therein [64][65][66][67]. The involvement of Trp3 in interfacial activation was confirmed by fluorescence measurements [68,69]. Likewise, the four N-terminal residues of ppPLA 2 were found to be unstructured in the solution structure, but were "immobilized" by micelle binding [19,21].…”
Section: Native State Dynamicsmentioning
confidence: 99%
“…(Reviews of the literature concerning this topic are given in [1,2,8,10,13,15,17].) The decay of the fluorescence of proteins can usually be represented as a sum of two or three exponential components.…”
Section: Nonexponential Fluorescence Decaymentioning
confidence: 99%
“…There is one qualitative observation that seems to be relevant to this issue and this suggests a connection between quenching and kinetic complexity. We have found [1,8,17] that in quite a few cases (not restricted to T4 lysozyme), the fluorescence decay complexity is greater for those cases where the quantum yield is low. This suggests that there is a connection between collisional quenching and fluorescence decay complexity.…”
Section: Conclusion and Speculationsmentioning
confidence: 99%